Comparison of salivary immunoglobulin A levels in children delivered by cesarean section with those delivered via vaginal delivery - Priya Subramaniam; Shilpy Dwivedi; K L Girish Babu (Wolters Kluwer Medknow Publications, 2016)
Background: Salivary immunoglobulin A (SIgA) is an important factor in the oral defense mechanism. SIgA levels in infants have shown to vary widely. Mode of delivery may influence SIgA levels. The present study was conducted to evaluate levels of SIgA in infants at different ages, and to compare it with the mode of delivery. Methodology: The study group consisted of 279 healthy neonates and infants up to the age of 9 months. They were divided according to age: Group I: 6-10 days; Group II: 6-8 weeks; Group III: 6 months, and Group IV: 9 months. Unstimulated whole saliva was collected from the floor of the mouth and buccal sulcii by means of sterile polyethylene pipettes. Saliva was collected 1 h after feeding. All salivary samples were collected in disposable sterile vials and transferred suitably to a laboratory for estimation of SIgA level using enzyme-linked immunosorbent assay. Data were subjected to statistical analysis. Results: There were 146 infants that were delivered by cesarean section and 133 vaginally delivered infants. There was a significant difference in the SIgA levels between vaginal delivery and cesarean section infants (P < 0.001). Conclusion: Mode of delivery appears to have influence on the levels of SIgA in saliva of neonates and infants.